Socio-environmental indicators in the integrated river basin management at the Sorocaba metropolitan region, São Paulo state, southeastern Brazil - Leinfelder, Fernanda Maria Soares Urquieta; Tonello, Kelly Cristina; Leal, Mariana Santos; Correa, Carina Júlia Pensa (Sociedade & Natureza, 2019)
We aimed to diagnose the current status of water resources at the seven river basins that form the Sorocaba Metropolitan Region (SMR) in São Paulo state, southeastern Brazil, by using indicators that would enable us to identify socio-environmental issues. Indicators of demography and social responsibility, water quality, water supply and demand, as well as state and response indicators of sanitation services, were obtained for the SMR basins. Three basins are strongly compromised in terms of environmental indicators, and two of them also underperformed on social indicators, despite the high local wealth. The three basins that have low wealth, low urbanization rate and low demographic density yielded good or intermediary values for social indicators, yet two of those basins should be given special attention, as they were revealed to be having issues related not only to water supply and demand but also to water pollution. Lastly, the basin that harbors the largest water supply in the region yielded good values for environmental indicators, yet it also yielded poor results for social ones. As the SMR basins have diverse features, their integrated management may pose a huge challenge, insofar as it should meet different social, economic and environmental needs that are necessary for development. In that sense, the present study should contribute to identifying actions that should be taken at the municipal and regional scales to foment sustainable development in the region.